Ответы 2

  • Ответ:

    x = 1

    Пошаговое объяснение:

    (4х+28)•1,2+1,3•(х+3)+(-1,7-6,1)=35,8

    4,8x + 33,6 + 1,3x + 3,9 - 7,8 = 35,8

    6,1x + 29,7 = 35,8

    6,1x = 35,8 - 29,7

    6,1x = 6,1

    x = 6,1 : 6,1

    x = 1

    • Автор:

      dunn85
    • 5 лет назад
    • 0
  • .........................
    answer img
    • Автор:

      lane63
    • 5 лет назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years